2009
DOI: 10.2105/ajph.2007.128090
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perceived Discrimination and Obesity in a Population-Based Multiracial and Multiethnic Adult Sample

Abstract: These findings are not completely unsupported. White ethnic groups including Polish, Italians, Jews, and Irish have historically been discriminated against in the United States, and other recent research suggests that they experience higher levels of perceived discrimination than do other Whites and that these experiences adversely affect their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
182
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(196 citation statements)
references
References 66 publications
10
182
3
1
Order By: Relevance
“…Prior research using the same dataset as our study finds that perceived discrimination is linked with increased obesity (Gee et al, 2008). However, there may be racial and ethnic variation in the association between discrimination and body mass (Hunte & Williams, 2009). …”
Section: Perceived Discriminationmentioning
confidence: 65%
“…Prior research using the same dataset as our study finds that perceived discrimination is linked with increased obesity (Gee et al, 2008). However, there may be racial and ethnic variation in the association between discrimination and body mass (Hunte & Williams, 2009). …”
Section: Perceived Discriminationmentioning
confidence: 65%
“…Discrimination has been associated with more depressive symptoms (34), poorer mental health (4-6, 17), poorer sleep (35,36), increased adiposity (12)(13)(14)37), higher blood pressure (9)(10)(11), inflammatory biomarkers (15,16), and subclinical CVD (7,8). However, studies of discrimination and CVD risk factors are not unequivocal (2,17).…”
Section: Discussionmentioning
confidence: 99%
“…Two scales with documented reliability and validity in diverse samples (12,(23)(24)(25)(26)(27) were used to measure perceived discrimination at baseline. The Lifetime Discrimination Scale, adapted from the Detroit Area Study (23), asked respondents to report whether they had ever been treated unfairly (yes/no) in 6 domains: being fired from a job or denied a promotion; not being hired for a job; being treated unfairly by the police; being discouraged by a teacher/advisor from continuing one's education; being prevented from moving into a neighborhood by a landlord or realtor; and having life made difficult by neighbors.…”
Section: Discrimination Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have found associations between self-reported racism and coping mechanisms such as smoking, alcohol consumption, and substance use for White populations, suggesting that the underlying process of racism as a stressor can result in coping mechanisms of maladaptive health behaviors regardless of race/ethnicity. 50,51 In addition, other studies have found null associations among minority racial/ethnic groups. 31,32,51 This study may be underpowered to assess modest associations between self-reported racism and these behaviors with adjustment for a variety of sociodemographic factors among non-White racial/ethnic groups, and it may be overpowered to assess these associations for Whites, thus finding even the weak effects statistically significant.…”
Section: Self-reported Racism and Cancer-related Behaviorsmentioning
confidence: 99%